Taxes as a factor of Kazakhstan’s competitiveness improvement (Journal of Economic Research & Business Administration, 2016)
Tax system is one of the main instruments of national economy’s regulation and defining priorities of social and economic development. The state, ably using instruments of tax mechanism, changing tax policy, on the assumption of priority tasks of economy development, has possibility as to stimulate economic growth, also to to improve it. State tax regulation influences on favorable business climate and creates possibilities for innovative activity. Kazakhstan government constantly elaborates, corrects tax legislation with the purpose of creating world-class tax system. Till recent times changes of tax legislation mainly concerned following directions: reviewing tax rates and tax benefits, changing amount and types of taxes and other compulsory payments to the budget, correcting of particular parameters of tax control etc. At the same time the system of tax process management practically has not been changed and needs to be improved. In this context, tax system as very important element of market relations in many ways defines success of economic reforms in the country and the level of country’s competitiveness.
Keywords: tax system; tax policy of the state; economy’s competitiveness improvement.